INTERNALIZATION OF THE VALUES OF RELIGIOUS CHARACTER IN LEARNING ACTIVITIES AS AN EFFORT OF CHARACTERISTICS ISLAMIC MANNERS - Wawang Haerudin; Tajuddin Noor (al-Afkar, Journal For Islamic Studies, 2022)
This research is motivated by the phenomenon of the progress of the times that change the way of life and human interaction, with the help of current technology it is easier to violate the norms of society and religion. Therefore, it is necessary to fortify oneself with religious character values. This study uses a type of library research research, namely research conducted through data collection and scientific writing that aims to solve a problem.  The results of the study indicate that the internalized religious character values ​​are the Illahiyyah values ​​(related to God) and the Insaniyyah values ​​(related to humans). The steps used consist of three stages, namely the value transformation stage, the value transaction stage, and the value transinternalization stage. The method used is a direct and indirect method, through separate subjects and integrated into all subjects, through activities outside the subject, namely habituation or self-development, through example (uswah hasanah), through advice and pay attention as well as reward and punishment methods.